دراسة عن تخطيط تدريس اللغة العربية فى الجامعة الإسلامية - Fathul Maujud (At-Ta'dib, 2017)
Development of education curriculum and instruction in language shows the need of the society to learn the language either to meet personal or social needs. And to meet those needs someone can study alone or through educational institutions. Needs of society related to language skills often change depending on the conditions of them, it is necessary to hold a coordination of language teaching in order to be able to meet those needs. Therefore, every teacher should plan before teaching. Some important things in learning the language include: 1) Arabic Language Teaching requires preparation and planning of good learning, teaching is likened to a process consisting of three elements that complement each other, namely: learning objectives, learning process, and evaluation of learning outcomes . 2) teachers should manage the desired language skills acquired after the end of the teaching process. 3) knowing about the needs of each student in every teaching program, and tailored to the teaching objectives that have been determined by each institution.